Bond behaviour of ribbed near-surface-mounted iron-based shape memory alloy bars with short bond lengths. (June 2020) - Schranz, Bernhard; Czaderski, Christoph; Vogel, Thomas; Shahverdi, Moslem
Abstract: Many existing concrete buildings worldwide require improvement in structural integrity. Previous research has proven the effectiveness of iron-based shape memory alloy (Fe-SMA or memory-steel) reinforcements for the prestressed strengthening of structures. The unique function of the material, i.e., the so-called shape memory effect, enables cost-effectiveness and presents simple ways to prestress defective building components. Ribbed memory-steel bars have only been available recently. This study aimed to investigate their performance in a novel strengthening technique, named near-surface mounted (NSM) method. Bond experiments with short bond lengths were performed to investigate the feasibility of this configuration and to identify the effects of several design parameters including: groove dimensions, bar diameter, bar material, cover depth, mortar strength, and concrete strength. The use of a digital image correlation system enabled detailed measurements of slips, crack width, and surface strain. An analytical procedure based on the differential equation of bond behaviour was developed, which enabled the calculation of slip, strain, bond shear stress, and load capacity. The results show that ribbed memory-steel bars can be used in an NSM configuration due to high bond capacity. The cover depth, substrate strength and elastic modulus had a significant effect on the failure mode and bond capacity. Graphical abstract: Unlabelled Image Highlights: Three pull-out failure modes were revealed: splitting, combined splitting and pull-out, splitting of the cube. The failure modes mainly depend on cover depth, mortar and concrete strength, and bar diameter. Longitudinal splitting cracks were observed with an image correlation system during experiments with low cover depth. Stainless steel bars showed lower bond strength than memory-steel bars with non-linear stress-strain behaviour. Analytical modelling reproduced bond stress, bar strain, and slip, as well as load capacity of the bonded joint.